Pilihan Rasional Masyarakat Lamongan dalam Memilih Bank Syari’ah - Amelia, Ihdina Shofia; Fauzi, Agus Mahfud (MOMENTUM : Jurnal Sosial dan Keagamaan, 2021)
Syari'ah bank is one of the places to store wealth that uses the teachings of the Islamic religion as a financing mechanism, but still uses business principles for profit. The emergence of syari'ah banks is a special attraction for some people. This research focuses on how the rationality of the Islamic community in Islam. Lamongan in choosing syari'ah bank as a place to invest wealth. The theory used in this research is James S. Coleman about rational choice. This research uses qualitative methods, in which the types, sources, techniques, and data analysis are carried out in a descriptive way so that the results of the research obtained are in accordance with the phenomena that occur in the field. The results of this study indicate that there are several factors that cause the Lamongan Islamic community to choose syari'ah banks as a place for wealth investment. Shari'ah banks were chosen for simple reasons, friendly service, accurate information services, and profitable shari'ah business calculations. In addition, there are syari'ah banks that provide young hajj savings services so that they can be used as a long-term investment and a means of worship